Ticks (Acari: Ixodidae) as ectoparasites of Brazilian wild birds and their association with rickettsial diseases - Ogrzewalska, Maria; Pinter, Adriano (Brazilian Journal of Veterinary Research and Animal Science, 2016)
Ticks (Acari: Ixodidae) are obligatory hematophagous ectoparasites of a variety of vertebrate hosts and play an important role in the transmission and ecology of infectious pathogens causing diseases in humans and animals worldwide. Sixty-eight species of ticks exist in Brazil, and at least 23 are found parasitizing wild birds. This number is increasing with the advent of new studies highlighting the underestimated role of birds in the life cycle of these arthropods. In South America, many of these ticks are involved in epidemiology of the life-threatening spotted fever diseases caused by bacteria from the genus Rickettsia (Rickettsiales: Rickettsiaceae). The aim of this paper is to present up-to-date knowledge about the bird-tick fauna of Brazil and their association with rickettsioses. The available literature concerning ticks on birds and tick-borne diseases related to these ticks in Brazil has been revised. It could be concluded that birds play a primary role in life cycles of various tick species, especially during immature stages (larvae and nymphs). The best known is a bird-tick fauna from the Atlantic Forest and from Brazilian savannah called Cerrado in southern and central Brazil, respectively. On the other hand, the knowledge about bird tick parasitism from other Brazilian biomes such as the Amazon, Caatinga, Pantanal and Pampas regions is very scarce and requires further study. Moreover, no studies about the role of birds as mobile hosts for spreading ticks to new areas exist, nor has their role in the natural life cycle of Rickettsia been thoroughly examined.